An Analysis of Efficiency and Productivity Changes in Indonesian Islamic Banks During 2018-2023: A Dea-Malmquist Index Approach - Pramestya, Shri Embun Rinjani Kasih; Aji Purba Trapsila (Islamic Economics and finance in Focus, 2025)
This study analyzes the efficiency and productivity of Indonesian Islamic banks from 2018 to 2023 using Data Envelopment Analysis (DEA) and Malmquist Index. Results show fluctuations in operational efficiency and productivity growth, influenced by external factors like the COVID-19 pandemic and technological progress. Despite increasing total assets, some years experienced efficiency declines, indicating internal management challenges. Technological innovation significantly boosts productivity, but internal inefficiencies persist post-pandemic. The study recommends adopting advanced technology, digital transformation, and continuous efficiency evaluation to enhance competitiveness. Strengthening regulation for risk management and innovation is also essential. Limitations include reliance on secondary financial data, focus on specific financial metrics, and a relatively short observation period, which restrict comprehensive long-term trend analysis amid external uncertainties.